DIFFERENT FERTILIZATION SYSTEMS IN THE PRODUCE OF MAIZE IN FUNCTION OF AGRICULTURE SUSTAINABLE AND RURAL AREAS - Cvijanović, Gorica; Cvijanović, Drago; Subić, Jonel (Economics of Agriculture, 2006)
Fertilization, as agro-technical step, is irreplaceable in the process of achieving high yields. However, in the aim of sustainable agriculture and rural settlements, it is necessary to establish which systems of fertilization in the function of protecting biodiversity could be implemented in maize production. That is why an experiment was established with different systems and ways of fertilization and during this test hybrid ZP 704 was grown. There was implemented dressing with mineral nitrogen with two doses (125 and 270 kg N/ha), to ploughed maize (in amount of 8 000 kg/ha) as an organic matter and mix of mineral nitrogen (both of dose) and ploughed maize. Also, in the part of the test in which inoculation seeds before sewing was implements, as liquid inoculums there are composite of effective race next class: Azotobacter chroococcum, Azospirillum lipoferum, Klebsiella planticola, Beijerinckia Derx. They diagnosed that search parameters (amount of organic substance, the level transformation of organic substance in the organic substance of the soil, index of total nitrogen and yield seed of maize, were increase quite in the different combination ploughed maize and mineral nitrogen). In process of inoculation of seeds, searched elements of the essential mineral elements of soil (total amount of micro-organisms, bacterium scale from period cycle nitrogenous) in minimum and middle dose application mineral nitrogenous had maximum values. It is concluded that for protection of biodiversity and economical organic food production, application mineral dressing could be correct with plough organic substance or with implement diazotrof-a, and in that occasion the amount of mineral nitrogen could be reduce for 40 kg/ha.